Cardiolipin and Its Different Properties in Mitophagy and Apoptosis - Li, Xiao-Xiao (J Histochem Cytochem, 2015)
Cardiolipin (CL) is a unique dimeric phospholipid that exists almost exclusively in the inner mitochondrial membrane (IMM) in eukaryotic cells. Two chiral carbons and four fatty acyl chains in CL result in a flexible body allowing interactions with respiratory chain complexes and mitochondrial substrate carriers. Due to its high content of unsaturated fatty acids, CL is particularly prone to reactive oxygen species (ROS)-induced oxidative attacks. Under mild mitochondrial damage, CL is redistributed to the outer mitochondrial membrane (OMM) and serves as a recognition signal for dysfunctional mitochondria, which are rapidly sequestered by autophagosomes. However, peroxidation of CL is far greater in response to severe stress than under normal or mild-damage conditions. The accumulation of oxidized CL on the OMM results in recruitment of Bax and formation of the mitochondrial permeability transition pore (MPTP), which releases Cytochrome c (Cyt c) from mitochondria. Over the past decade, the significance of CL in the function of mitochondrial bioenergy has been explored. Moreover, approaches to analyzing CL have become more effective and accurate. In this review, we discuss the unique structural features of CL as well as the current understanding of CL-based molecular mechanisms of mitophagy and apoptosis.